Sustainable Concrete Technology in the Field of Transmission Infrastructure: A Review - Prajapati, Neeraj Kumar; Gurjar, Sita; Meena, Hitesh; Biswal, Monalisha (Journal of Progress in Civil Engineering, 2024)
The increasing demand for energy and the imperative shift towards sustainable infrastructure have propelled research efforts towards developing eco - friendly materials for critical applications such as power transmission projects. This abstract provides a comprehensive overview of the current state of sustainable concrete technologies tailored specifically for power transmission infrastructure. The study delves into the environmental impact of conventional concrete used in such projects and explores innovative approaches to enhance sustainability. The review encompasses various aspects, including the incorporation of alternative binders such as fly ash, slag, and silica fumes, as well as the optimization of mix designs to reduce carbon footprint. Special attention is given to the performance, durability, and long - term resilience of sustainable concrete in comparison to traditional counterparts. Moreover, the document discusses the economic feasibility of implementing sustainable concrete in power transmission projects, considering factors such as material cost, construction practices, and life - cycle analysis. The abstract concludes with insights into ongoing research trends and potential future developments in sustainable concrete technologies, emphasizing the need for collaborative efforts between academia, industry, and policymakers to promote environmentally conscious practices in the realm of power transmission infrastructure, taking into account desired power transmission best performance.